Relationship between dietary intake and atherogenic index of plasma in cardiometabolic phenotypes: a cross-sectional study from the Azar cohort population - Shirin Soheilifard; Elnaz Faramarzi; Reza Mahdavi (Journal of Health, Population and Nutrition)
Abstract Background Cardiovascular diseases are a leading cause of global mortality, with diet playing a key role in their progression. The Atherogenic Index of Plasma (AIP) is a predictive marker for cardiovascular risk, but its association with dietary intake across cardiometabolic phenotypes remains underexplored. This study investigates the relationship between dietary intake and AIP, hypothesizing that energy intake and macronutrients influence AIP and, consequently, cardiovascular risk. Methods This cross-sectional study analyzed data from 9,515 participants aged 35–55 in the Azar cohort study. Based on Body Mass Index (BMI) and metabolic syndrome (MetS), participants were classified into four phenotypes: metabolically healthy normal weight (MHNW), metabolically unhealthy normal weight (MUHNW), metabolically healthy obese (MHO), and metabolically unhealthy obese (MUHO). Dietary intake was evaluated using a semi-quantitative food frequency questionnaire (FFQ), and AIP was calculated. Adjustments were made for age, gender, socioeconomic status, and physical activity. Results A notable difference was observed in demographic and clinical status between cardiometabolic groups of males and females. The AIP was highest in the MUHNW (0.42 for males; 0.28 for females) and lowest in the MHNW (0.05 for males; -0.05 for females, P < 0.001). There was a statistically significant difference in the mean energy intake and the percentage of energy intake from protein among the cardiometabolic phenotypes (p < 0.001). After adjusting for confounders, only weak but meaningful correlations remained for energy, carbohydrate, and protein intake in the MUHO (r = 0.048, P = 0.01; r = 0.057, P = 0.003; and r = 0.050, P = 0.01) and for carbohydrate and lipid intake in the MHO (r = 0.034, P < 0.01 and r = -0.055, P < 0.001). Conclusion The study found weak but meaningful correlations between energy, carbohydrate, and protein intake and AIP in the MUHO phenotype and between carbohydrate and lipid intake and AIP in the MHO phenotype. This highlights the role of energy and carbohydrates in AIP within specific subgroups. Future research should focus on the effects of macronutrient combinations on AIP and long-term dietary impacts on metabolic health instead of BMI.